ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN DAN NIAT PENGGUNAAN BERKELANJUTAN APLIKASI E FILLING - Ari, Dessanti Putri Sekti; Ferinda Nabilah Putri (FIA UB, 2022)
One application of e-government at the Directorate General of Taxes is the e-filing application. E-filing is one of the Directorate General of Taxes applications that help online SPT reporting. E-filing can help taxpayers report their SPT more efficiently and faster. However, there are still some taxpayers who do not use this application. The system is successful if the user is sure to continue using it again. Therefore, this study aims to determine the effect of e-filing service quality on user satisfaction and the effect of user satisfaction on sustainable intentions. The population used in this study is individual taxpayers on the island of Java. The sampling method used is accidental sampling. This study used an online survey to collect data. The results of this study indicate that efficiency, public support, and trust have a significant effect on user satisfaction. User satisfaction itself has a significant effect on ongoing intentions in e-filing applications. Reliability has no significant effect on user satisfaction.